2016
DOI: 10.1039/c5cc09878e
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of a marginally stable disilenyl germylene to tricyclic systems: evidence for reversible NHC-coordination

Abstract: Tetrasiladigermatricyclohexanes in two isomeric forms (chair and doubly-bridged tetrahedron) are obtained by the reaction of MeLi with an α-chlorosilyl functionalized NHC-stabilized silagermenylidene. (29)Si NMR at low temperature proves the initial formation of a monomeric NHC-adduct of a disilenyl germylene followed by cyclisation to the isomeric heavy cyclopropene. Addition of an excess of NHC stabilizes the both intermediates and demonstrates the reversibility of rate-determining initial equilibria involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Silicoids have been used as starting material for homoatomic silicon clusters or heteroatomic silicon‐germanium clusters. Reactions of Li[Si 2 (Tip) 3 ] with [GeCl 2 ]⋅dioxane result in the formation of [Si 4 Ge 2 (Tip) 6 ] (Tip=2,4,6‐tri‐isopropylphenyl), which was obtained either as a six‐membered ring or a cluster compound shielded by the six ligands (Figure ) . By addition of [GeCl 2 ]⋅NHC′ (NHC′=1,3‐diisopropyl‐4,5‐dimethylimidazol‐2‐ylidene), the authors isolated [SiCl(Tip) 2 ‐Si(Tip)=GeNHC′] that might be viewed as resulting from an 1,3‐Cl shift of the proposed intermediate [Si(Tip) 2 =Si(Tip)‐GeCl], which was stabilized as [Si(Tip) 2 =Si(Tip)‐GeCl(NHC′)].…”
Section: Formation Of Ligand‐protected Metal Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…Silicoids have been used as starting material for homoatomic silicon clusters or heteroatomic silicon‐germanium clusters. Reactions of Li[Si 2 (Tip) 3 ] with [GeCl 2 ]⋅dioxane result in the formation of [Si 4 Ge 2 (Tip) 6 ] (Tip=2,4,6‐tri‐isopropylphenyl), which was obtained either as a six‐membered ring or a cluster compound shielded by the six ligands (Figure ) . By addition of [GeCl 2 ]⋅NHC′ (NHC′=1,3‐diisopropyl‐4,5‐dimethylimidazol‐2‐ylidene), the authors isolated [SiCl(Tip) 2 ‐Si(Tip)=GeNHC′] that might be viewed as resulting from an 1,3‐Cl shift of the proposed intermediate [Si(Tip) 2 =Si(Tip)‐GeCl], which was stabilized as [Si(Tip) 2 =Si(Tip)‐GeCl(NHC′)].…”
Section: Formation Of Ligand‐protected Metal Clustersmentioning
confidence: 99%
“…Further NMR studies were undertaken on mixed Ge/Si clusters (Figure ) . The NHC adduct [Si 2 (Tip) 3 ClGeNHC′] (after 1,3‐chlorine shift of the precursor Si 2 GeR 3 Cl, c.f.…”
Section: Formation Of Ligand‐protected Metal Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands. In particular, for the heavier carbon analogue silicon, a plethora of studies reported new low-valent compounds in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the chemistry of silylene base adducts has already been carefully developed [14,[26][27][28][29][30][31][32][33][34][35][36]. Before these findings, silyliumylidene ions, cationic Si(II) species were found to be promising as similar versatile Lewis amphiphiles [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Scheschkewitz et al have taken a similar approach with the synthesis of the multiply functional NHC-coordinated silagermenylidenes, I and II (Scheme 1) [16,17], which serve as precursors for cyclic NHC-coordinated germylenes of type III, IV, and V under consumption of the Si=Ge bond, but retention of the low-valent germanium center (Scheme 1) [16,18,19]. The leaving group characteristics of the peripheral chloro functionality of II can be exploited for the incorporation of different organic substituents by treatment with organolithium reagents in order to fine-tune the steric requirements of the ligand scaffold of cyclic germylenes of type IV [20,21]. Directly chloro-functionalized silylenes and germylenes are readily converted to a variety of novel low-valent group 14 compounds by functional group interconversion at the low-valent tetrel center [22].…”
Section: Introductionmentioning
confidence: 99%